2014
DOI: 10.1039/c3bm60276a
|View full text |Cite
|
Sign up to set email alerts
|

Fracture-based micro- and nanofabrication for biological applications

Abstract: While fracture is generally considered to be undesirable in various manufacturing processes, delicate control of fracture can be successfully implemented to generate structures at micro/nano length scales. Fracture-based fabrication techniques can serve as a template-free manufacturing method, and enables highly-ordered patterns or fluidic channels to be formed over large areas in a simple and cost-effective manner. Such technologies can be leveraged to address biologically-relevant problems, such as in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 77 publications
(156 reference statements)
0
23
0
Order By: Relevance
“…Subsequently, cells attached specifically to these agents and formed web patterns. The crack dimensions and their geometries could be tailored through the applied force and prepatterning of the layer, respectively . Linear cracks of dimensions smaller than the cell diameters were used to investigate rapid unidirectional cell growth by similarity to growth along an extracellular matrix …”
Section: Guiding Organismsmentioning
confidence: 99%
“…Subsequently, cells attached specifically to these agents and formed web patterns. The crack dimensions and their geometries could be tailored through the applied force and prepatterning of the layer, respectively . Linear cracks of dimensions smaller than the cell diameters were used to investigate rapid unidirectional cell growth by similarity to growth along an extracellular matrix …”
Section: Guiding Organismsmentioning
confidence: 99%
“…Besides, due to regular cracking, an array of nanochannels (the cracks with tens of nanometers in width) was produced, as shown in Fig. 3(g), which might be of potential applications in biology as nanofluid devices [45][46][47][48].…”
Section: Characterization Of Splatsmentioning
confidence: 99%
“…With the substrate stretched perpendicularly to that direction a crack is formed at the soft island’s tip (see Figure 1). While other groups have used large aspect ratio surface patterns like notches to start cracks [26,27,28], the soft islands presented here are the first planar patterns used for that purpose. We have found that the strain needed for that crack formation increases with increasing curvature radius of the island’s tip.…”
Section: Introductionmentioning
confidence: 99%